Adapting to the sea: Human habitation in the coastal area of the northern Netherlands before medieval dike building. (1st May 2019) - Nieuwhof, A.; Bakker, M.; Knol, E.; de Langen, G.J.; Nicolay, J.A.W.; Postma, D.; Schepers, M.; Varwijk, T.W.; Vos, P.C.
Abstract: Before medieval dike building, the coastal area of the northern Netherlands was a wide, regularly inundated salt-marsh area. Despite the dynamic natural conditions, the area was inhabited already in the Iron Age. The inhabitants adapted to this marine environment by living on artificial dwelling mounds, so-called terps. Terp habitation was a highly successful way of life for over 1500 years, and may be re-introduced as a useful strategy for present and future communities in low-lying coastal regions that are facing accelerated sea-level rise. This already has been recommended in several reports, but detailed knowledge of the technology of terp habitation is usually lacking. The aim of this paper is to present nearly two decades of archaeological research in the coastal region of the northern Netherlands, in order to inform the current debate on the possibilities of adapting to the effects of climate change in low-lying coastal areas. It presents the multi-disciplinary methods of this research and its results, supplying details of terp construction and other strategies such as the construction of low summer dikes that are still useful today. The results and discussion of the presented research also make it possible to describe the conditions that must be met to make terp habitation possible. Terp habitation could have continued, were it not for the considerable subsidence of inland areas due to peat reclamation. That made the entire coastal area increasingly vulnerable to the sea. In response to this threat, dike building began in the 11th or 12th century, but these increasingly higher dikes decreased the water storage capacity and caused impoundment of seawater during storm surges. Moreover, accretion through sedimentation was halted from then on. Unlike terp habitation, the construction of high dikes therefore cannot be considered a sustainable solution for living in low-lying coastal areas in the long term. Highlights: Terp habitation has ensured save living in a salt marsh landscape for over 1500 years. Terp habitation may be applicable in low-lying coastal areas all over the world. Gas and salt extraction or drainage of peat should be avoided in low coastal areas. Dikes and terps testify to very different mind sets. Terp habitation is necessarily based on community effort and shared responsibility.